A 12-bp indel in the 3'UTR of porcine CISH gene associated with Landrace piglet diarrhea score. (September 2022) - Niu, Buyue; Chen, Zhihua; Yao, Diwen; Kou, Mingxing; Gao, Xiaowen; Sun, Yuan; Yang, Xiuqin; Wang, Xibiao; Di, Shengwei; Cai, Jiancheng; Guo, Dongchun
Abstract: Variations in Cytokine inducible SH2-containing protein (CISH) gene influence human susceptibility to common infectious diseases, but little is known about CISH in swine. The objectives of this study were to 1) determine porcine CISH (pCISH) mRNA expression level in different tissues of piglets, 2) predict putative functional genetic variations within pCISH, 3) investigate the association between a identified variation in the 3'UTR and piglets phenotype traits in Min ( n = 226) and Landrace ( n = 186) population, and explore the function of this variation. Results of quantitative PCR showed pCISH mRNA expressed in all the collected tissues with higher level in lung and ileum than colon ( p < 0.05). In-silico analysis indicated none of the functional ns-SNPs existed in pCISH coding region. Results from the characterizing of 3'UTR presented a novel 12-bp insertion/deletion (indel) mutation. Statistical analysis demonstrated that this 12-bp indel associated with piglets diarrhea score in the Landrace population, and animals with AA genotype (12-bp insertion) presented lower diarrhea score when compared with BB ( p < 0.05) or AB ( p < 0.01) carriers. The in vitro study indicated that the luciferase activity of reconstruct plasmid psiCHECK-2-CISH-AA or psiCHECK-2-CISH-BB was significantly lower than the negative control ( p < 0.05), and luciferase activity of psiCHECK-2-CISH-AA was higher than that of the psiCHECK-2-CISH-BB ( p < 0.05). Although results herein suggested the 12-bp indel might affect Landrace piglet susceptibility to diarrhea, further association studies in more populations are needed before this preliminary finding could be used for pig breeding. Highlights: The mRNA expression of porcine CISH was higher in the ileum of SPF piglets. The diarrhea score of Landrace piglets carrying the 12-bp insertion was low. The 12-bp indel identified in the 3'UTR of porcine CISH affected the mRNA stability.